Abstract Phonology in a Concrete Model : Cognitive Linguistics and the Morphology-Phonology Interface. - Nesset, Tore (Cognitive Linguistics Research, v. 40., 2008)
This book is relevant for phonologists, morphologists, Slavists and cognitive linguists, and addresses two questions: How can the morphology-phonology interface be accommodated in cognitive linguistics? Do morphophonological alternations have a meaning? These questions are explored via a comprehensive analysis of stem alternations in Russian verbs. The analysis is couched in R.W. Langacker's Cognitive Grammar framework, and the book offers comparisons to other varieties of cognitive linguistics, such as Construction Grammar and Conceptual Integration. The proposed analysis is furthermore compa.